The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/jvi.76.15.7578-7586.2002
|View full text |Cite
|
Sign up to set email alerts
|

Viral Gene Expression Patterns in Human Herpesvirus 6B-Infected T Cells

Abstract: Herpesvirus gene expression is divided into immediate-early (IE) or ␣ genes, early (E) or ␤ genes, and late (L) or ␥ genes on the basis of temporal expression and dependency on other gene products. By using real-time PCR, we have investigated the expression of 35 human herpesvirus 6B (HHV-6B) genes in T cells infected by strain PL-1. Kinetic analysis and dependency on de novo protein synthesis and viral DNA polymerase activity suggest that the HHV-6B genes segregate into six separate kinetic groups. The genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
2
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 39 publications
7
45
2
2
Order By: Relevance
“…Transcripts derived from 12 of the 41 genomic regions tested were detected in the CHX-treated sample. Detection of B7, U79 and G91/B8 (which corresponds to the 59 untranslated region of U90) under IE conditions is in agreement with previously published data (Oster & Hollsberg, 2002;Schiewe et al, 1994;Taniguchi et al, 2000). Several previously unclassified transcripts including B2, U85, G86/90.2 and G86/ 90.3 were also detected under IE conditions.…”
Section: Analysis Of Hhv-6b Ie Transcriptionsupporting
confidence: 79%
See 3 more Smart Citations
“…Transcripts derived from 12 of the 41 genomic regions tested were detected in the CHX-treated sample. Detection of B7, U79 and G91/B8 (which corresponds to the 59 untranslated region of U90) under IE conditions is in agreement with previously published data (Oster & Hollsberg, 2002;Schiewe et al, 1994;Taniguchi et al, 2000). Several previously unclassified transcripts including B2, U85, G86/90.2 and G86/ 90.3 were also detected under IE conditions.…”
Section: Analysis Of Hhv-6b Ie Transcriptionsupporting
confidence: 79%
“…The late cluster consisted of genes expressed only at times after 24 h p.i. Among this group of genes, U11, U22, U23, U47 and U100 have been described previously as L genes (French et al, 1999;Mirandola et al, 1998;Oster & Hollsberg, 2002).Although these data showed good agreement with the known temporal order of many HHV-6 genes, the kinetics of some remained poorly defined, especially for the early cluster, which contains a mixture of IE and E genes. To better define the transitions between IE-to-E and E-to-L genes, viral gene expression in cells treated with CHX (protein synthesis inhibitor) and PAA (DNA synthesis inhibitor) was analysed for the classification of IE and E/L genes, respectively.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…The virus then replicates, assembles, and exits the infected cell to infect other cells. The first proteins synthesized during viral replication are the immediate-early (IE) proteins [16] . It was recently reported that two proteins, IE1 and IE2, distinguish the variants, HHV-6A and HHV-6B, respectively (L. Flamand, abstract 3-2, 6th International Conference on HHV6 & 7, 2008).…”
Section: Pathophysiologymentioning
confidence: 99%